Comparing the Effectiveness of Cognitive Behavioral Couple Therapy and EIS Model on Sexual Function, Among Pregnant Women - Mohammad Amini; Mahmoud Guodarzi; Shole Shahgheibi (Hamadan University of Medical Sciences, 2021)
Background and Objective: Pregnancy causes many physical and psychological changes. Therefore, pregnant women may face many issues and problems, including a lack of reduced sexual function. This study was prepared to compare the effectiveness of cognitive-behavioral couple therapy training and the EIS (empathy, intimacy, and sexual satisfaction) model on sexual function in pregnant women. Material and Methods: This was a semi-experimental study with pre- and post-test design. A total of 60 people among the statistical population, who met the inclusiojn criteria were chosen, and randomly divided into three groups of 20 (two intervention groups and one control group). The intervention participants were trained using cognitive-behavioral and EIS model in 8 sessions of 90 minutes, while the control group did not receive any training during this time. The tool used to collect data in pre- and post-test was the Women's Sexual Performance Index (FSFI). Data were analyzed using SPSS 23 at a significance level of 0.05. Results: Findings showed that both cognitive-behavioral approaches and the EIS model are practical on sexual function and its subscales (sexual desire, sexual arousal, vaginal moisture, orgasm, sexual satisfaction, painful intercourse) (P<0.05). There is a difference in their effectiveness in this regard. The EIS model with a mean and standard deviation of 24.08 ± 1.85 had a more significant effect on sexual function than the cognitive-behavioral approach with a mean and variation of 17.58 ±1.1. Conclusion: Therefore, it can be concluded that despite the differences between these two approaches (cognitive-behavioral approaches and EIS model), both are useful in terms of sexual function and its subscales. However, due to the greater effectiveness of the EIS model, it can be used during pregnancy besides the other cares.